Transcriptomic profile of aguR deletion mutant of Lactococcus lactis subsp. cremoris CECT 8666 - Beatriz del Rio; Daniel M. Linares; Begoña Redruello; Maria Cruz Martin; Maria Fernandez; Anne de Jong; Oscar P. Kuipers; Victor Ladero; Miguel A. Alvarez (Genomics Data, 2015)
Lactococcus lactis subsp. cremoris CECT 8666 (formerly GE2-14) is a dairy strain that catabolizes agmatine (a decarboxylated derivative of arginine) into the biogenic amine putrescine by the agmatine deiminase (AGDI) pathway [1]. The AGDI cluster of L. lactis is composed by five genes aguR, aguB, aguD, aguA and aguC. The last four genes are responsible for the deamination of agmatine to putrescine and are co-transcribed as a single policistronic mRNA forming the catabolic operon aguBDAC [1]. aguR encodes a transmembrane protein that functions as a one-component signal transduction system that senses the agmatine concentration of the medium and accordingly regulates the transcription of aguBDAC [2], which is also transcriptionally regulated by carbon catabolic repression (CCR) via glucose, but not by other sugars such as lactose and galactose [1,3]. Here we report the transcriptional profiling of the aguR gene deletion mutant (L. lactis subsp. cremoris CECT 8666 ∆aguR) [2] compared to the wild type strain, both grown in M17 medium with galactose as carbon source and supplemented with agmatine. The transcriptional profiling data of AguR-regulated genes were deposited in the Gene Expression Omnibus (GEO) database under accession no. GSE59514.